2013
DOI: 10.1007/s00467-013-2538-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroprotection for hepatitis B in children with nephrotic syndrome

Abstract: Based on our results, we conclude that children with SRNS are less likely to seroconvert with vaccination. A higher dose (double) of hepatitis B vaccine should be used for vaccinating such patients. Anti-HBs titers should be monitored in SRNS patients post-vaccination, and a booster should be given if titers fall to <10 mIU/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…Similar results were found in a study by Mantan M, et al who observed more anti-HBS titre with double dose (20µg) of vaccine than with normal dose (10µg) of vaccine in SSNS 11 . In our study, the mean HB vaccine titre was significantly higher in children receiving 20µg HB vaccine compared to those receiving 10µg.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were found in a study by Mantan M, et al who observed more anti-HBS titre with double dose (20µg) of vaccine than with normal dose (10µg) of vaccine in SSNS 11 . In our study, the mean HB vaccine titre was significantly higher in children receiving 20µg HB vaccine compared to those receiving 10µg.…”
Section: Discussionsupporting
confidence: 90%
“…In the study by Mantan M, et al, only 37% children with NS on non-steroid immunosuppression had seroprotective titres after HB vaccine in comparison with 76% only on steroids 11 . A four-dose schedule (0, 1, 2, 12 months) or double the normal dose at the routine intervals can overcome this 11,12 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, a cross-sectional study that examined protection against HBV in 33 children with SSNS found that only 63.6 % patients had protective antibody levels [22]. Patients who had received the vaccine as part of their routine childhood vaccination schedule had higher antibody titers than those who received the vaccine after onset of NS, despite the latter group receiving a double dose [22].…”
Section: Patients Receiving Steroidsmentioning
confidence: 88%
“…Patients who had received the vaccine as part of their routine childhood vaccination schedule had higher antibody titers than those who received the vaccine after onset of NS, despite the latter group receiving a double dose [22]. Two other studies have shown that the response to vaccination with HBV is lower in children with SSNS (63-67 % seroconversion after 3 doses) than in healthy children, particularly in those on 2 mg/kg/day of prednisolone, even if the vaccine is administered in remission [23,24].…”
Section: Patients Receiving Steroidsmentioning
confidence: 91%